Wasilah Renderforest Fi Tadris Al-Mufrodat Li Thalabah As-Shaf Ats-Tsamin Fi Al-Madrasah Al-Tsanawiyah Al-Hukumiyah 1 Payakumbuh - Mulya Rahmy Umar (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2022)
The main problem in this study is "Does Renderforest media affect improving students’ skill in mufrodat of class VIII MTsN 1 Payakumbuh?". This study aims to know students' skills in mufrodat before using Renderforest media, to know its use, and to know its effect on the skill in mufrodat of class VIII MTsN 1 Payakumbuh. The research methodology used in this study is an experimental research methodology with a quantitative approach and the type of field research. The data collection instrument used a test. The researcher analyzed the data using SPSS 20. The researcher found that the data were normally distributed and homogeneous with a significance value of > 0.05 as a requirement for the T-test. The results showed that the use of Renderforest media affected the student's skill in mufrodat of class VIII MTsN 1 Payakumbuh. This can be seen from the difference in the average mufrodat scores of students before using Renderforest media and after. Student learning outcomes before using the media Renderforest were 60.68 and after 85.83. Meanwhile, based on the T-test, the value of Sig. (2-tailed) 0.000 is smaller than 0.05 and the calculated T-value (-12, 164) is greater than the table T-value (-20, 935). So, the researcher concludes that Ho is rejected and Ha is accepted. So, Renderforest media has a significant effect on the student's skill in mufrodat of class VIII MTsN 1 Payakumbuh.